Priority Micronutrient Density of Foods for Complementary Feeding of Young Children (6–23 Months) in South and Southeast Asia - Ortenzi, Flaminia; Beal, Ty (Frontiers in Nutrition, 2021)
Abstract Background: Given their high nutrient requirements and limited gastric capacity, young children during the complementary feeding period (6-23 months) should be fed nutrient-dense foods. However, complementary feeding diets in low- and middle-income countries are often inadequate in one or more essential micronutrients. In South and Southeast Asia infants’ and young children’s diets are commonly lacking in iron, zinc, vitamin A, folate, vitamin B12 and calcium, hereafter referred to as priority micronutrients. Objective: This study aimed to identify the top food sources of priority micronutrients, among minimally processed foods for complementary feeding of children (6-23 months) in South and Southeast Asia. Methods: An aggregated regional food composition database for South and Southeast Asia was built, and recommended nutrient intakes (RNIs) from complementary foods were calculated for children aged 6-23 months. An approach was developed to classify foods into one of four levels of priority micronutrient density based on the calories and grams required to provide one-third (for individual micronutrients) or an average of one-third (for the aggregate score) of RNIs from complementary foods. Results: We found that the top food sources of multiple priority micronutrients are organs, bivalves, crustaceans, fresh fish, goat, canned fish with bones, and eggs, closely followed by beef, lamb/mutton, dark green leafy vegetables, cow milk, yoghurt, and cheese, and to a lesser extent, canned fish without bones. Conclusions: This analysis provided insights into which foods to prioritize to fill common micronutrient gaps and reduce undernutrition in children aged 6-23 months in South and Southeast Asia.